2001
DOI: 10.1590/s0034-71082001000200006
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity assessment of benthic macroinvertebrates in altitudinal lotic ecosystems of Serra do Cipó (MG, Brazil)

Abstract: Five lotic systems of Serra do Cipó, south-east Brazil, were investigated in order to assess the existing diversity of benthic macroinvertebrates, habitats-microhabitats, and the available trophic resources. For each river it was analysed the communities of benthic macroinvertebrates and the composition of some taxonomic groups (Plecoptera, Ephemeroptera, Trichoptera and Diptera Chironomidae): the community with Bivalvia Sphaeriidae, Oligochaeta and Ephemeroptera Baetidae (being supposed a closed relation Biva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0
9

Year Published

2001
2001
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 2 publications
(2 reference statements)
3
18
0
9
Order By: Relevance
“…Os coletores que foram os organismos mais freqüentes em ambos locais, também foram mais numerosos em rios de correnteza e de altitude e em lagoas da região serrana de Minas Gerais, Brasil (JACOBSEN & ENCALADA 1998, MARQUES et al 1999, REMPEL et al 2000, CALLISTO et al 2001a, GALDEAN et al 2001.…”
Section: Eixo2 (15%)unclassified
See 1 more Smart Citation
“…Os coletores que foram os organismos mais freqüentes em ambos locais, também foram mais numerosos em rios de correnteza e de altitude e em lagoas da região serrana de Minas Gerais, Brasil (JACOBSEN & ENCALADA 1998, MARQUES et al 1999, REMPEL et al 2000, CALLISTO et al 2001a, GALDEAN et al 2001.…”
Section: Eixo2 (15%)unclassified
“…Alguns estudos têm investigado a estrutura da comunidade dos invertebrados bentônicos e as variáveis físicas e químicas dos rios brasileiros, destacando-se os trabalhos realizados no Estado de São Paulo por UIEDA & GAJARDO (1996), BRAN-CO & NECCHI JR. (1997), KIKUCHI & UIEDA (1998), no Rio de Janeiro por BAPTISTA et al (1998) e BAPTISTA et al (2001a e em Minas Gerais por MARQUES et al (1999), CALLISTO et al (2001) e GALDEAN et al (2001. Para as bacias hidrográficas do Rio Grande do Sul, no entanto, não há dados disponíveis até o momento.…”
unclassified
“…At all sites, the typical dominance of Chironomidae and Baetidae was observed (Pinder, 1986;Suren, 1994;Galdean et al, 2001;Ferrington, 2008). The sensitive families e.g.…”
Section: Discussion -Conclusionmentioning
confidence: 83%
“…Previous studies on stream ecosystems in the headwaters of Serra do Cipó and Serra da Canastra National Parks showed that Corynoneura was very abundant (GALDEAN et al 1999b(GALDEAN et al , 2001. Corynoneura was normally found on surfaces covered by filamentous algae, mosses and debris (GALDEAN et al 1999 a, b).…”
Section: Resultsmentioning
confidence: 97%